Dominants of economic security of Russian industrial organizations with participation of state in capital: chronicles of “Russian Helicopters” holding company - A. V. Savin (Вестник университета)
Measures and activities of the Russian state aimed at ensuring the economic security of the "Russian Helicopters" holding company have been considered. The problematic situations in the company’s activities that threaten its stable functioning have been presented. The development of the model range of "Russian Helicopters" in comparison with leading foreign competitors has been reviewed. The technological parity of the holding and competing firms has been diagnosed. The efforts of the Russian state to meet the needs of Russian helicopter builders in aircraft engines and new materials have been described. A group offactors influencing the level of unit cost has been presented. The production results of the holding’s work have been given. It has been concluded about the effectiveness and efficiency of the actions of the management and the state-owner of the company, aimed at protecting its interests.